Metode Tahsin Al-Qur’an Santri Baru di Dayah Ummul Ayman Samalanga Kabupaten Bireuen - Nabawi, Nabawi (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2022)
Tahsin Qur’an learning carried out at two traditional Islamic boarding schools, Dayah Ummul Ayman Samalanga, still face a number of issues, such as the tahsin management not properly organized, the role of the teacher not yet optimized, and the learning methods applied by the tahsin teachers not well performed. The purpose of this study was to investigate the methods of learning tahsin Qur’an at Dayah Ummul Ayman Samalanga. This study was a type of descriptive research utilizing a qualitative approach. Data collection was carried out by using observation, interview, and documentation methods. The data were then analyzed by involving data collection, data reduction, data display, and conclusion drawing. The results showed that, the tahsin leaning methods applied at Dayah Ummul Ayman Samalanga included the lecture method, the mudarasah method, the talaqqi method, the sima’i method, the recitation method, and the muraja’ah/takrir method.